Analisis Kepuasan Pengguna Terhadap Layanan Aplikasi Brimo Menggunakan Mobile Service Quality dengan Metode CSI - Dini Andini; Joy Nashar Utamajaya (STMIK Budi Darma, 2023)
BRImo currently presents a variety of services that will make it easier for its users to make banking transactions. The problem with this research is that system errors often occur and based on reviews on the Google Playstore, there are many responses from users to the application. Users also provide positive responses and negative responses in the form of complaints given by users, one of which is the access speed when using the BRImo application. Users also feel disappointed in the application so that interest in using the application decreases. Because there are still a number of complaints and unsatisfactory ratings, it is necessary to conduct research on user satisfaction in order to find out how high user satisfaction is with the BRImo application. The method used in this study uses the Customer Satisfaction Index (CSI) method to measure the percentage of satisfaction of BRImo application users. This study will use the dimensions contained in mobile service quality which have been modified to suit the object studied in this study. The data used to be processed in this study were obtained from the results of a questionnaire with a total of 15 questions. Respondents in this study amounted to 100 respondents. After collecting data from respondents, the data will be tested for validity and reliability in order to find out how valid and reliable the data will be processed later using the CSI method. The results of this study can be seen in the calculation of the CSI method, the percentage of user satisfaction is 81.33% and it can be stated that customers feel